Optimisasi Multi-Objektif Pada Pelayanan Kesehatan Di Ruang Rawat Inap Rumah Sakit - Alamsyah, Arif; Sari, Rina Filia (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
This research focuses on optimizing healthcare services to find the optimal values for inpatient ward capacity and room allocation for patients to enhance the efficiency and quality of healthcare services in hospitals. The method employed in this study is the multi-objective optimization method with two objective functions. The solution is executed using the simplex method with the POM application on the Windows operating system. Hospitals face challenges managing limited resources, including inpatient ward space and staff, while ensuring timely and effective patient care. This study addresses these challenges using a multi-objective optimization approach that simultaneously considers multiple objectives. The research considers several key factors, such as the number of incoming and outgoing patients, the capacity of inpatient ward rooms, and the initial diagnosis of patients' health conditions. By optimizing these variables, the research aims to identify the most efficient way to allocate resources and maximize patient care quality. The research results indicate that the optimal capacity for accommodating patients in the Inpatient Ward of Mitra Medika Hospital is 1,400.88 patients, with a minimum requirement of 48 rooms for inpatient care. This optimization improves resource utilization and enhances patient satisfaction by reducing wait times and ensuring the availability of the appropriate facilities for their needs.